Policaptil Gel Retard in adult subjects with the metabolic syndrome: Efficacy, safety, and tolerability compared to metformin. Issue 3 (May 2021) - Guarino, G.; Della Corte, T.; Strollo, F.; Gentile, S.
Abstract: Background: Policaptil Gel Retard® (PGR), is a new macromolecule complex based on polysaccharides slowing the rate of carbohydrate and fat absorption. It proved to significantly reduce body weight, acanthosis nigricans expression, HbA1c levels, and glucose metabolism abnormalities in obese, hyper-insulinemic adolescents. No such data are available for adults. Aim: to compare the effects of PGR vs. metformin in adult subjects with the Metabolic Syndrome (MS) and T2DM on a Low Glycemic Index diet. Subjects and methods: This spontaneous clinical, longitudinal, single-blind, randomized study based on a per-protocol analysis enrolled 100 outpatients with MS and T2DM consecutively referring to our clinic for three months, and randomly assigned to either the active treatment (Group A :, 6 tablets/day) or the comparator (Group B : Metformin tablets, 1500–2000 mg/day in two divided doses during the two main meals, to minimize side effects) to be taken 30 min before each main meal in equally divided doses. Serum lipid profile, anthropometry, HOMA-IR index, and tolerability parameters were evaluated before and after a 6-month follow-up period. Results: all parameters improved at a similar rate in both groups but for the lipid profile, which got even better in Group A. Group A also experienced less prominent gastrointestinal side effects than its counterpart. Conclusion: For the first time, we showed the non-inferiority of PGR compared to metformin in obese adult subjects with the MS and T2DM as for glycemic control and a clear-cut superiority of PGR in terms of both serum lipid-lowering capacity and tolerability. Highlights: Treatment of metabolic syndrome needs more drugs this makes adherence to treatment worse. Metformin is the most widely used drug for glycemic control but its gastrointestinal side effects are well known. Policaptil gel retard is a medical device made of substances (MDMS), reducing plasma glucose and body weight. Policaptil gel retard is proposed as a useful alternative to metformin in the treatment of metabolic syndrome.